Influence of technological factors on the properties of oil-fat composition (OFC KTIOL) - Yarmolitska, Olena; Oseiko, Мykola; Romanovska, Tetiana (My University, 2019)
Wool grease is a natural lipid that softens the skin and sheep's wool fibers, as well as protects them from adverse weather conditions. The most widely used products are refined wool oil and its modifications, which are called lanolin. Lanolin and its derivatives have a wide range of applications. The work is devoted to the study of the oxidation characteristics of oil-fat composition during the thermal oxidation process.
Keywords: lanolin; fat oxidation; antioxidant properties; ланолін; окиснення жирів; антиоксидантні властивості; кафедра технології жирів, хімічних технологій харчових добавок та косметичних засобів